Deep Sequencing Study of the MTHFR Gene to Identify Variants Associated with Myelomeningocele - Aneji, Chiamaka U (2012)
INTRODUCTION: Neural tube defects (NTDs) are congenital anomalies caused by a combination of genetic and environmental influences. A defect below the head region resulting in protuberance of meninges and nervous tissue is termed myelomeningocele (MM). MM, the most common NTD compatible with survival, occurs in approximately 1 in 1,000 births worldwide. Maternal pre- and periconceptional folate supplementation reduces the risk of NTDs by up to 70%. A key enzyme in folate metabolism is 5, 10-methylene-tetrahydrofolate reductase (MTHFR). OBJECTIVES: Sequence the 12 exons of the MTHFR gene among 96 subjects with MM to identify variants potentially contributing to the disease trait. METHODS: Exons were amplified by polymerase chain reaction and the products were sequenced by Sanger method to reveal sequence variants compared to MTHFR reference sequences. Association of variants was examined by Fisher’s test. RESULTS: A novel variant c.171+3G>T was identified in intron 1 in one affected subject. The variant was not found in the subject’s unaffected mother’s DNA and the unaffected father’s DNA was unavailable. We found significant differences in allele frequencies for seven SNPs in MM subjects compared to ethnically matched reference populations reported in the single nucleotide polymorphism (SNP) database (dbSNP). CONCLUSION: We identified a novel variant c.171+3G>T in the MTHFR gene that potentially affects splicing in an affected subject. Also, we observed five SNPs (rs13306561, rs2274976, rs2066462, rs12121543, and rs1476413) in the MTHFR gene not previously shown to associate with MM. The current study provides additional evidence that multiple variations in the MTHFR gene are associated with MM.